Penerapan Metode PDCA dan 5 Why Analysis pada WTP Section di PT Kebun Tebu Mas - Wirawan, Endik; Minto (INVANTRI (Inovasi Dan Pengelolaan Industri), 2021)
Sugar is one of the basic needs of the Indonesian people. For the sake of the running of national sugar, the sugar industry competition will also be tighter. Therefore it is important for sugar industry players to always maintain and improve quality as well as PT Kebun Tebu Mas. One of the efforts to maintain quality is by making continuous improvements. The WTP division in the Boiler division at PT Kebun Tebu Mas often experiences several problems including Replace the Cartridge Filter (28%), Mossy Filter Cleaning Cartridge (69%) and several other problems. By applying the PDCA Method and 5 Why Analysis, the results obtained are that the two main problems decreased to 16% and 14%. This means that quality has no impact on the value of quality.